On lower bounds for the widths of classes of functions defined by integral moduli of continuity - Derets, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish lower bounds for the Kolmogorov widths d 2n-1(W r H 1 ω .L p ) and Gel’fand widths d 2n-1(W r H 1 ω .L p ) of the classes of functions W r H 1 ω with a convex integral modulus of continuity ω(t).